Perkembangan Perpustakaan Islam Pada Masa Dinasti Bani Umayyah - M. Nur Rahmat Achdar AT.; Muh. Quraisy Mathar; La Ode Ismail Ahmad (LPPM IAIN Sorong, 2024)
The Umayyad dynasty pioneered the development of Islamic libraries during its reign. This article aims to find out the reasons for the establishment and development phases of Islamic libraries during the Umayyad Dynasty. This research is a type of library research with descriptive qualitative analysis. The approach used is a hostorist and normative-descriptive approach. Data were collected and processed using heuristic, criticism, interpretation, and historiography techniques. The results of this study show that: 1) the cause of the establishment of the Islamic library during the Umayyad Dynasty was started by Yazid bin Khalid who realized the urgency of science. He then called the Greeks in Egypt to translate books into Arabic to complete the library collection. 2) The development phase of the Islamic library during the Umayyad Dynasty was influenced by the power and scientific tradition of Syria, the development of culture, and the library.